2020
DOI: 10.3329/bju.v23i1.50293
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between Silodosin alone and Silodosin plus Tadalafil for the medical management of lower Ureteric Stone in South-Western part of the Bangladesh

Abstract: Objective: To compare the treatment outcome of Silodosin alone and Silodosin plusTadalafil as a medical expulsive therapy (MET) of lower ureteric stone in south-westernpart of Bangladesh. Methodology: The study was conducted in a tertiary hospital in Khulna, over a periodof 12 months (January 2019 to December 2019). Out of 108 patients, 100 meet theinclusion criteria who were purposively assigned into 2 groups. 48 patients included inSilodosin alone group and 52 in Silodosin plus Tadalafil group. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…Side effects significantly differed between the studied groups (P < 0.001 and stone size (the bigger stone size, the less expulsion, OR = 0.292, 95% CI = 0.171 -0.498, P < 0.001) (Table 4). and that this rate is statistically higher than that of either drug alone (tamsulosin or Silodosin) (7) Regarding the number of pain episodes in our present study showed an overall significant difference between the studied groups, there was an overall statistically significant difference between the three studied groups (p < 0.001). We also found that the number of hospital visits due to pain was significantly showed significantly fewer emergency room visits.…”
Section: Resultscontrasting
confidence: 45%
See 1 more Smart Citation
“…Side effects significantly differed between the studied groups (P < 0.001 and stone size (the bigger stone size, the less expulsion, OR = 0.292, 95% CI = 0.171 -0.498, P < 0.001) (Table 4). and that this rate is statistically higher than that of either drug alone (tamsulosin or Silodosin) (7) Regarding the number of pain episodes in our present study showed an overall significant difference between the studied groups, there was an overall statistically significant difference between the three studied groups (p < 0.001). We also found that the number of hospital visits due to pain was significantly showed significantly fewer emergency room visits.…”
Section: Resultscontrasting
confidence: 45%
“…the amount of analgesics required for pain also showed statistically significant difference between the three groups, with lower amount of diclofenac sodium in group C (median = 450 mg) than in groups B (median = 675 mg) and C (median = 450 mg), with no significant difference between groups A and B. Similarly, two studies found that the combination of silodosin and tadalafil resulted in significantly fewer pain episodes than silodosin and tadalafil alone (P<0.001)(7,9). Also, another study showed significantly fewer episodes of pain with tadalafil plus tamsulosin as compared to tamsulosin alone(10), similarly a recent study demonstrated that patients in the tamsulosin plus tadalafil group had fewer pain episodes (2.02) compared to the tamsulosin group (2.32) (P value = 0.001) and…”
mentioning
confidence: 86%